2010
DOI: 10.1155/2010/724861
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of the Cerebellum to Cognition in Spinocerebellar Ataxia Type 6

Abstract: This study sought evidence for a specific cerebellar contribution to cognition by characterising the cognitive phenotype of Spinocerebellar Ataxia Type 6 (SCA-6); an autosomal dominant genetic disease which causes a highly specific late-onset cerebellar degeneration. A comprehensive neuropsychological assessment was administered to 27 patients with genetically confirmed SCA-6. General intellectual ability, memory and executive function were examined using internationally standardised tests (Wechsler Adult Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 62 publications
3
21
1
Order By: Relevance
“…Thus, failure to find significant correlations for any of the tests in the present study could be due to insufficient variability, either behavioral or in gray matter, in the population under study. This is likely the reason why our correlation results for digit span were not as robust as those reported by Cooper et al (37). …”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Thus, failure to find significant correlations for any of the tests in the present study could be due to insufficient variability, either behavioral or in gray matter, in the population under study. This is likely the reason why our correlation results for digit span were not as robust as those reported by Cooper et al (37). …”
Section: Discussioncontrasting
confidence: 76%
“…Previous SCA6 patient studies have demonstrated specific cognitive deficits in patients with this largely cerebellar pattern of degeneration, pointing to the role of the cerebellum in intellectual abilities (36,37). Cooper et al (2012) examined the correlation between cerebellar gray matter density and cognitive performance in a group of 15 SCA6 patients, demonstrating a relationship between verbal working memory and gray matter density in superior and inferior parts of the cerebellum.…”
Section: Discussionmentioning
confidence: 88%
“…One alternative explanation for the difference in performance between patients and controls could be based on cognitive demands and the recent implication of the cerebellum in cognition (26)(27)(28)(29). This appears unlikely, as the single-interval timing tasks are less demanding than those of beat-based timing, and as the cognitive deficits demonstrated in patients with cerebellar damage were specific to aspects of executive function or attention (27)(28)(29) and would not lead to the present dissociation.…”
Section: Discussionmentioning
confidence: 86%
“…This appears unlikely, as the single-interval timing tasks are less demanding than those of beat-based timing, and as the cognitive deficits demonstrated in patients with cerebellar damage were specific to aspects of executive function or attention (27)(28)(29) and would not lead to the present dissociation.…”
Section: Discussionmentioning
confidence: 89%
“…They emphasize the role of the cerebellum in executive functions [2,3], working memory [4,5], language competence [6][7][8][9][10], dyslexia [11], visuospatial abilities [12,13].…”
Section: Introductionmentioning
confidence: 99%